2007
DOI: 10.1038/sj.leu.2404772
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABLT315I transcript disappearance in an imatinib-resistant CML patient treated with homoharringtonine: a new therapeutic challenge?

Abstract: Our results are superior to results reported from large multicentre trials (DFS 29-39%). Our study is a relatively large, single-center study involving patients with a low median age at diagnosis. Outcome is often superior in single-center studies compared to multicenter studies, and age is a well-recognized prognostic factor. However, these factors cannot fully account for our favorable results. Our treatment protocol is rather intensive and contains more glucocorticoids, vincristine, L-asparaginase, methotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…A recent larger worldwide epidemiologic study has demonstrated the severity and the heterogeneity of this disease. 2 The therapeutic options for such patients remain few and are confined to untargeted therapies such as hydroxyurea, interferon-␣, 14 or omacetaxine mepesuccinate (formerly homoharringtonine), [14][15][16][17] which provide only short-term and mostly hematologic responses with poor cytogenetic efficacy. 17 Recently, a phase 1 trial with a third-generation TKI, ponatinib, provided very promising data.…”
Section: Resultsmentioning
confidence: 99%
“…A recent larger worldwide epidemiologic study has demonstrated the severity and the heterogeneity of this disease. 2 The therapeutic options for such patients remain few and are confined to untargeted therapies such as hydroxyurea, interferon-␣, 14 or omacetaxine mepesuccinate (formerly homoharringtonine), [14][15][16][17] which provide only short-term and mostly hematologic responses with poor cytogenetic efficacy. 17 Recently, a phase 1 trial with a third-generation TKI, ponatinib, provided very promising data.…”
Section: Resultsmentioning
confidence: 99%
“…Omacetaxine has demonstrated activity against cells with the T315I mutation in preclinical studies, 13 as well as preliminary efficacy in CML patients with this mutation. 14,15 Here, we describe the results of a phase 2 study of omacetaxine in chronic-phase CML patients with a history of the T315I mutation who failed TKI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Giles et al 11 reported 3 patients with T315I ϩ CML or Ph ϩ ALL who achieved clinical responses to the aurora kinase inhibitor MK-0457 without associated adverse events, whereas Legros et al 12 reported that the T315I mutation disappeared in a CML patient treated with homoharringtonine. In addition, it has been reported that some CML patients harboring a T315I mutation may have a transient response to second-generation TKIs in vivo.…”
Section: Introductionmentioning
confidence: 99%